Innovation in Maintaining Sampyong Oral Tradition in Cijati Village, Majalengka Regency - Ardh, Muhammad Reyhan Emirel; Syahrial, Syahrial (International Journal of Social Service and Research, 2023)
This research is a research on Sampyong Majalengka Performing Arts which has experienced changes in form, grip, and shifts in function. Abah Uu / Ki Anom Aduy Mangkubumi is a figure of Sampyong Karang Kamuning Sirah Dayeuh Cijati Majalengka, who innovates and modifies. The innovation resulted in various reactions and responses from the community, including Sampyong players, community leaders and the government. This study explains the form of invention, Abah Uu's strategy, and the community's response to creation. The method used is the Ethnographic Method. This method is used in the data retrieval process. The result found was Abah Uu's innovative form in the central Sampyong performance with the addition of different dance moves with Authentic Sampyong. Abah Uu gave the modification a name with the term Sampyong Budaya. Other modifications are changes in the package and function. Abah Uu makes the scary Sampyong into a witty entertainment, with collaborations with other arts in the form of dangdut pop sound art, and koplo. Various responses to the innovation include from the Grumala community, Padepokan Ki Braja Manggala, Padepokan Dangiang Luhur, and several community leaders. They consider that Sampyong is preserved in authentic form. Meanwhile, Padepokan Dangiang Luhur Nini joined the Abah Uu community. Abah Wastiam invaded Sampyong with the Sampyong Ujung version.